2014
DOI: 10.1017/s1751731113001869
|View full text |Cite
|
Sign up to set email alerts
|

Higher preweaning mortality in free farrowing pens compared with farrowing crates in three commercial pig farms

Abstract: If loose-housed farrowing systems are to be an alternative to traditional farrowing crates, it is important that they can deliver the same production results as can be achieved in farrowing crates under commercial conditions. The aim of this study was to compare preweaning mortality in farrowing crates and free farrowing pens (FF-pens) within herds that had both systems. The study was conducted over 2 years in three commercial Danish herds that had FF-pens as well as traditional farrowing crates in their farro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 30 publications
4
49
2
2
Order By: Relevance
“…Using similar farrowing pens with integrated crates as used in this study, Moustsen et al (2013) observed a higher piglet mortality rate in pens where sows were loose-housed throughout the whole lactation period than in those that were crated during the first 4 or 7 days pp; suggesting that crating for just 4 days pp is sufficient to avoid unnecessary crushings. Comparing farrowing crates with free farrowing pens, Hales et al (2014) found greater mortality rates in pens than in crates, even though pen sizes were, at 5.3 to 6.3 m 2 , considerably larger than in this as well as the aforementioned study. Contrarily, Weber et al (2007) found similar mortality rates in crates and loose-farrowing systems;…”
Section: Performancecontrasting
confidence: 40%
See 4 more Smart Citations
“…Using similar farrowing pens with integrated crates as used in this study, Moustsen et al (2013) observed a higher piglet mortality rate in pens where sows were loose-housed throughout the whole lactation period than in those that were crated during the first 4 or 7 days pp; suggesting that crating for just 4 days pp is sufficient to avoid unnecessary crushings. Comparing farrowing crates with free farrowing pens, Hales et al (2014) found greater mortality rates in pens than in crates, even though pen sizes were, at 5.3 to 6.3 m 2 , considerably larger than in this as well as the aforementioned study. Contrarily, Weber et al (2007) found similar mortality rates in crates and loose-farrowing systems;…”
Section: Performancecontrasting
confidence: 40%
“…In fact, this farrowing system was developed for intensive production systems, in which the abrupt change from continuous confinement as practiced at the moment to free farrowing is not an option; mainly due to increased management requirements. Even under optimized management regimen excessive piglet mortality might arise (Hales et al, 2014) and this limits the implementation of free farrowing pens in the field. Given the compromise between the ability of the sow to express its natural behaviour and the consequences this might have on the piglets in terms of crushings, the pen under study is able to provide the sow with a certain additional area to move and turn around, but not to the same extent as several of the recently developed free farrowing pens exceeding sizes of 5 m 2 (Weber et al, 2007;Hales et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations